Alcohol withdrawal syndrome: mechanisms, manifestations, and management. (1st September 2016) - Jesse, S.; Bråthen, G.; Ferrara, M.; Keindl, M.; Ben‐Menachem, E.; Tanasescu, R.; Brodtkorb, E.; Hillbom, M.; Leone, M.A.; Ludolph, A.C.
Abstract : The alcohol withdrawal syndrome is a well‐known condition occurring after intentional or unintentional abrupt cessation of heavy/constant drinking in patients suffering from alcohol use disorders (AUDs). AUDs are common in neurological departments with patients admitted for coma, epileptic seizures, dementia, polyneuropathy, and gait disturbances. Nonetheless, diagnosis and treatment are often delayed until dramatic symptoms occur. The purpose of this review is to increase the awareness of the early clinical manifestations of AWS and the appropriate identification and management of this important condition in a neurological setting.